Caecal diverticulitis can be misdiagnosed as acute appendicitis: a systematic review of the literature. (3rd August 2021) - Uhe, Isabelle; Meyer, Jeremy; Viviano, Manuela; Naiken, Surrennaidoo; Toso, Christian; Ris, Frédéric; Buchs, Nicolas C.
Abstract: Aim: Caecal diverticulitis (CD) is an uncommon condition which can be misdiagnosed as acute appendicitis due to similar clinical presentations. Further, its management varies among medical centres. The aim of this study was to review cases of patients with CD, to identify the factors differentiating CD from acute appendicitis and to provide a summary of existing diagnostic methods and therapeutic alternatives regarding its management. Methods: This systematic review was conducted in accordance with the PRISMA guidelines and the AMSTAR2 checklist. We searched MEDLINE and Embase from inception until 1 October 2018 for original publications reporting cases of CD. Results: Out of the 560 identified studies, 146 publications (988 patients) were included in the qualitative synthesis. Most frequent symptoms of CD were right iliac fossa pain (93.2%), nausea and/or vomiting (35.4%) and fever (26.9%). A total of 443 patients (44.8%) underwent radiological imaging, which reported CD in 225 patients (22.8%). For the other patients, the diagnosis was obtained by surgical exploration (73.9%). Among patients diagnosed with CD by imaging, 67 (29.8%) underwent surgery and 158 (70.2%) were treated conservatively. Among patients who underwent surgical exploration, treatment consisted most frequently of right hemi‐colectomy (33%), appendectomy (18.8%) and diverticulectomy with appendectomy (16.3%). Conclusion: CD can be misdiagnosed as acute appendicitis, therefore resulting in unnecessary surgical exploration. The review of the literature starting from 1930 highlights the critical role of medical imaging in supporting the clinician to diagnose this condition and administer adequate treatment.